Scale on Stress among Parents having only Daughters: Developing a Reliable Measure - Riaz, Saima; Fatima, Safoora; Aslam, Misbah; Salma, Umme (Pakistan Armed Forces Medical Journal, 2023)
Objective: To develop a reliable scale to measure stress among parents with only daughters. Study Design: Cross-sectional study. Place and Duration of Study: Department of Psychology, University of Gujrat, Gujrat Pakistan, from May to Jul 2019. Methodology: The study was conducted on parents who have only daughters. A pool of 59 items was created through brainstorming sessions and an intensive literature review. Afterwards, 42 items were retained through meticulous evaluation and assessment of experts. Subsequently, a scale was administered to 242 respondents who were selected through a purposive sampling technique. All the items were retained because of their high correlation with item total (r≥0.5). Exploratory factor analysis (EFA) and confirmatory factor analysis (CFA) proceeded for structure exploration and confirmation. Furthermore, the reliability of the scale was established. Results: EFA led to five factors encompassing 36 items. Moreover, CFA was carried out, and the model fit summary showed some indices in good ranges (RFI=0.923, NFI=0.940, GFI=0.928) while some in excellent ranges (CFI=0.970, IFI= 0.971, TLI=0.962) after the deletion of 22 items with significance p-value (0.001). The reliability of the scale was 0.93, while the reliability of the subscale ranges from 0.81 to 0.88. Conclusion: A reliable scale to measure Stress among parents having only daughters was successfully developed with 14 items casing four subscales.